The Effect Of Quality Product, Brand Image, And Price Towards A Purchase Decision Of J.Co Donuts & Coffee In Tangerang - Waseso Segoro; Debi Nurlita (Publisher Cv. Inara, 2021)
The development of the business world today is very fast, making business people have to compete with each other to attract consumers. One promising business is a business in the food sector such as donuts. Donuts are a type of food that is popular in Indonesian society. At present there are many donut outlets that stand in the center of the crowd. One of them is J.CO Donuts & Coffee in Tangerang which is the donut and coffee shop with the most consumers. With friendly prices and the brand image owned by J.CO Donuts & Coffee, consumers do not hesitate to buy their products.This study aims to determine the quality of the product, brand image and price of J.CO Donuts & Coffee purchasing decisions. The data used are primary data derived from questionnaires distributed online. Sampling using accidental sampling method with a sample size of 100 people. With the analysis technique used to analyze the influence of the variables in this study is to use the validity test, reliability test, classical assumption test, multiple regression analysis, and hypothesis testing using SPSS version 20. The result of this study is that there is a partial influence between variables of product quality, brand image and price on purchasing decisions. And the variables of product quality, brand image and price simultaneously influence purchasing decisions.